Some LIS Faculty Indicate Reservations about Open Access - Hayman, Richard (Evidence Based Library and Information Practice, 2016)
A Review of: Peekhaus, W., & Proferes, N. (2015). How library and information science faculty perceive and engage with open access. Journal of Information Science, 41(5), 640-661. http://dx.doi.org/10.1177/0165551515587855 Objective – To examine the awareness of, attitudes toward, and engagement with open access (OA) publishing, based on rank and tenure status among library and information science (LIS) faculty in North America. Design – Web-based survey distributed via email. Setting – Accredited library and information science (LIS) programs in North America. Subjects – 276 professors and professors emeriti. Methods – Researchers collected email addresses for 1,017 tenure-track, tenured, and emeriti professors from the public websites of the LIS programs. Researchers sent an email invitation to participate in the survey by accessing a URL, with the survey itself delivered using Qualtrics software. The survey included 51 total questions, some with additional sub-questions, and most items used Likert-type rating scale. The researchers analysed the data using SPSS software, and indicated using chi-square tests to measure significance, with a stated intent to get beyond the descriptive statistics commonly seen in other publications. Main Results – This study’s results draw on 276 completed responses, for a response rate of 27%. Researchers reported that 53% of respondents had some experience with publishing in a peer-reviewed OA format. When asked whether they agreed that scholarly articles should be free to access for everyone, pre-tenure assistant professors were most likely to agree (74%), followed by tenured associate professors (62%), full professors (59%) and then emeriti professors (8%). However, they found less likelihood that associate professors would have actually published in an OA format, highlighting a “disconnect between beliefs about accessibility of research and actual practice with open access” (p. 646). Researchers also discovered a connection between faculty awareness of institutional and disciplinary repositories and faculty publishing in OA journals, though a relatively low number (35%) had deposited their output in a repository within the previous year. That increases to 50% of respondents when timeframe is ignored. Faculty who had never published in OA journals ranked several barriers to doing so, barriers common across disciplinary boundaries. These include objections to paying OA fees; perceptions of slow time to publish, low research impact, and venue prestige when compared to traditional subscription journals; an inability to identify an appropriate OA journal; and an inability to pay OA fees. However, the researchers note that a majority of these respondents who had never published in an OA format would do so if these barriers were removed. Those participants who had some previous experience with OA were more likely to have positive perceptions of OA journal quality and impact, as well as the overall publishing experience, as compared to publishing in traditional journals. As in other disciplines, LIS faculty are conscious of the connection between OA and tenure and promotion processes. For example, this study reveals that non-tenured faculty are more likely to agree that publishing in OA venues may affect their career progress. Researchers report uncertainty about OA even among tenured LIS faculty. Of all respondents, only 34% agreed that a tenure or promotion committee might consider an OA publication on par with a traditional publication, while 44% of respondents were of the opinion that an OA publication would be treated less favourably than a traditional journal. A mere 1% of respondents believed that an OA publication would be treated more favourably within the tenure and promotion process. Despite this unfavourable perception of OA, the researchers report that 38% of respondents planned to publish in an OA journal regardless of whether their tenure and promotion committees might treat that OA publication unfavourably. Conclusion – The researchers report a connection between publishing in an OA journal and academic rank, with full professors more likely to publish OA or to have previous experience in publishing in an OA journal as compared to assistant professor colleagues, who perceive publishing in OA as a potential impediment to career progress. The researchers note that there is significant opportunity for LIS faculty involved in tenure and promotion committees to consider and clarify how OA publications are treated, and the impact of OA publishing with regard to career progress. Moreover, given the levels of uncertainty and equivocacy among faculty respondents as a whole regarding certain aspects of OA, the perceptions around quality and rigour, there is room for further research into LIS professors’ perceptions and attitudes toward open access, and how these change over time.